Compound Discovery and Structure-Activity Relationship Study of Neoantimycins Against Drug-Resistant Cancer Cells - Lin, Xiao; Zhou, Yongjun; Liu, Liyun; Zhu, Hongrui; Chen, Yeping; Wang, Shuping; Sun, Fan; Chai, Ling; Liu, Buming; Xu, Shihai; Lin, Hou-Wen (Frontiers in Chemistry, 2019)
Four neoantimycins H-K (1–4) with C1-keto, including the new ones (1–2), were isolated from the culture of Streptomyces conglobatus RJ8. After enzymatically converting into their respective reduced type derivatives (5–8) in vitro, the absolute structures of 1–8 were established/reconfirmed by analyzing hydrolyzed components. The obtained NATs (4, 7, and 8) exhibited excellent cytotoxicity against drug-resistant colon and gastric cancer cells but low toxicity in the noncancerous cell. Further SAR investigation suggested that C1-hydroxyl, C9-isobutyl, and N-formyl contribute to the antiproliferation remarkably.